Meat eaters - McClaren, Meredith (Oni Press, an Oni Press Publication, 2025)
"From cartoonist Meredith McClaren-co-creator of the acclaimed series Black Cloak-comes a punishing and poignant original graphic novel about the monsters that lurk both in the darkness beyond-and within us all . . . Let it be said that dying is hard. Nineteen-year-old Ashley Moore found this out the hard way. All Ashley wanted was to keep her head down and work hard until she could escape the small town where she felt she was stagnating. But after waking up one night covered in blood--and irrevocably dead--Ashley finds her foolproof plan for getting out has gone up in smoke, and something within her has changed. Without a heartbeat and with a disturbing craving for fresh--preferably bloody--meat, Ashley finds herself privy to a world that exists just beneath our own: a world of ghouls and monsters and things that go bump-in-the-night. Despite her desire to be left alone--and to not think about the night of her death at all-Ashley is slowly drawn into the realm of the unusual, getting advice from ancient vampires, dodging angry pack leaders, and becoming the reluctant big sister to werewolves Motley and Harrison. As she does, she finds it increasingly difficult to put away the parts of herself she wishes to ignore-namely, what happened that fateful night she stopped breathing. The truth, it turns out, can't stay buried forever. In this visceral story about the effects of trauma and anxiety, dying is indeed hard. But getting on with it? That can be worse"--